2016
DOI: 10.1093/ejcts/ezw168
|View full text |Cite
|
Sign up to set email alerts
|

Continuous paravertebral block for post-cardiothoracic surgery analgesia: a systematic review and meta-analysis

Abstract: A continuous paravertebral block is used when pain relief is required beyond the duration of a single-injection paravertebral block. Surgical procedures requiring an incision into the pleural cavity are some of the most painful procedures postoperatively and, if not managed appropriately, can lead to chronic pain. The current gold standard for post-cardiothoracic surgery pain management is epidural analgesia, which has contraindications, a failure rate of up to 12% and risk of complications such as epidural ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 41 publications
2
40
0
7
Order By: Relevance
“…Continuous PVB may be a solid alternative to TEA with equal analgesic effects. However, PVB is still a neuroaxial technique that carries some neurological risks in addition to the risk of technical failure in 6%–12% of cases (Scarfe et al, ). The selected technique, thoracic interfacial SAPB, is an excellent alternative to other locoregional analgesic techniques, in the authors’ opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous PVB may be a solid alternative to TEA with equal analgesic effects. However, PVB is still a neuroaxial technique that carries some neurological risks in addition to the risk of technical failure in 6%–12% of cases (Scarfe et al, ). The selected technique, thoracic interfacial SAPB, is an excellent alternative to other locoregional analgesic techniques, in the authors’ opinion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has shown that the paravertebral block has equivalent analgesic effects to epidural analgesia and is associated with a lower incidence of nausea, vomiting, hypotension, and urinary retention 15. However, the reported failure rate is 6–12%, and the risk of neurological damage should not be underestimated 16.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, as an alternative analgesic method, PVB is reported to have good pain-control efficacy and fewer side effects. A number of studies that compare PVB with EPI for thoracotomy and meta-analysis studies reveal PVB provides comparable analgesia with EPI and has better side effect profile (6,(8)(9)(10). Generally, EPI is blindly administered into the epidural space, and results in bilateral anesthesia.…”
Section: Commentsmentioning
confidence: 99%
“…Recently, paravertebral block (PVB) has been reported as an alternative to EPI (4)(5)(6)(7). PVB has equivalent analgesic effects to EPI and have a lower incidence of side effects, such as nausea, vomiting, hypotension and urinary retention (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%